PENGARUH PEMBELAJARAN ONLINE TERHADAP MOTIVASI BELAJAR MAHASISWA - Fadhila Zilfa Zen; Nova Susanti; Wina Tiodora Sinuraya; Ina Santia; Gustian Gustian (Didaktika : Jurnal Kependidikan, 2022)
The purpose of this study was to determine the effect of online learning on student learning motivation. This research uses quantitative research methods. The sampling technique used in this study was purposive sampling and the data collection technique in this study was using a questionnaire with a Likert scale measurement. The research instrument used a questionnaire distributed via a Google Form link to measure the effect of online learning on students' learning motivation. Based on the value of 2 = 0.641, 64.1% of the students' learning motivation of the Faculty of Teacher Training and Education is influenced by the online learning system implemented.Keywords:  Online learning, Covid-19, Learning Motivation, student